Acute haemorrhagic oedema of infancy with bullae and koebnerisation - Mohd Sazlly Lim, Sazlyna; Shamsudin, Norashikin (Academy of Family Physicians of Malaysia, 2014)
A 5-month-old Malay boy presented with purpuric papules and plaques on the face and extremities accompanied by fever, coryzal symptoms and bilateral lower limb oedema. There were also bullous linear purpuric lesions on the right upper limb. Blood and culture tests were normal. Histopathological tests showed leucocytoclastic vasculitis, confirming the diagnosis of acute haemorrhagic oedema of infancy. The patient achieved complete recovery after 2 weeks with no recurrence.